Nounself pronouns: 3rd person personal pronouns as identity expression - Miltersen, Ehm Hjorth (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2016)
This paper is an examination of and attempt at a preliminary definition of nounself pronouns, which are a large number of newly invented English 3rd person personal pronouns that have not been previously studied. The pronouns are created and used primarily by a virtual community on the blogging platform tumblr.com, with the first occurrence of a nounself pronoun in late 2013. The study is based on data from 134 responses to a questionnaire written by the author, distributed through tumblr.com, as well as on email-based interviews with three respondents who volunteered to be interviewed. Analysis of the data suggests that the pronouns are used to express, explore, and negotiate the identities of the respondents, in particular in relation to gender identities.